Les droits linguistiques canadiens en évolution - Fortier, D’Iberville (Les Cahiers de droit, 1986)
The Commissioner of Official Languages presents the evolution of linguistic rights from the time of Confederation up to the period of the Quiet Revolution in Québec. This survey dwells upon guarantees granted to linguistic minorities in Canada. At the Federal level of government, the author describes the consequences of the Royal Commission of Enquiry on Bilingualism and Biculturalism : The Official Languages Act and the Canadian Charter of Rights and Freedoms. At the provincial level of government, he draws up an overall account of the factual integration of these laws. His observations lead him to conclude that Canada will never be a homogeneous country with regard to linguistic rights and that minority aid systems are deficient. As a solution, the author underscores the timeliness of Federal-provincial arrangements with a view to creating specific development projects for official language minorities in accordance with local needs, but founded upon a common basis.